The Monro⁃Kellie doctrine for intracranial pressure - John ZHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
This laymen type of scientific history writing summarized the creation and development of Monro⁃Kellie doctrine and its potential role in intracranial hypertension. A Scottish scholar Monro created the concept of "intracranial pressure (ICP)" and his student Kellie supplemented Monro's concept, suggesting both cranial content and blood contributed to the ICP. Another Scottish scholar Abercrombie also studied ICP and in 1828 first used the term "Monro⁃Kellie doctrine". After establish the existence of cerebrospinal fluid, Burrows complemented further of the Monro⁃Kellie doctrine with cerebrospinal fluid. Over the last 200 years, the concept of ICP was recognized by physicians and used in clinical management of cranial disorders. DOI：10.3969/j.issn.1672⁃6731.2020.07.004